Effect of Furnace Heating Temperature on the Hardness and Corrosion Resistance of Plain Carbon Steel - Sopiyan Sopiyan; Syaripuddin Syaripuddin; Syamsuir Syamsuir; Fuad Ansori; Muhammad Yunan Hasbi; Ahmad Lubi; Ferry Budhi Susetyo (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
Microstructure modification of the plain carbon steel usually enhances hardness and corrosion resistance. Therefore, in the present research, the microstructure of plain carbon steel is modified by heating it in an electric furnace using various temperatures and then quenching it in engine oil to enhance corrosion resistance and hardness. Several characterizations were conducted, such as microstructure, hardness, and electrochemical behavior. The microstructure evolution indicates a clear transformation of martensite morphology with decreasing austenitizing temperature. Decreasing the furnace's heating before quenching could increase the specimens' hardness and corrosion resistance, with values around 586.36 HV and 0.135 mmpy. Therefore, the optimal heat treatment condition for plain carbon steel components in marine environments was found at 800 °C based on the results of this study.